Exodus : rezeptionen in deuterokanonischer und frühjüdischer Literatur - Gärtner, Judith, 1972-; Schmitz, Barbara, 1975- (Deuterocanonical and cognate literature studies, 2016)
The story of the Exodus from Egypt is one of the central traditions that are fundamental to the collective identity of Israel and permeate all of Old Testament literature. In the Hellenistic-Roman period, the Exodus tradition experienced a ›renaissance‹ and shaped contemporary literature as a figure of thought. These diverse exodus receptions are compiled for the first time in the anthology to form an overall view.